Pembelajaran Daring: Teknologi dan Inovasi untuk Meningkatkan Kualitas Pendidikan - Zukipli, Zukipli; Amri, Haerul; Irawaty, Irawaty; Bitu, Yuliana Sesi; Patty, Elyakim Nova Supriyedi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to explore the role of technology and innovation in optimizing online learning to enhance the quality of education. This study employs a qualitative approach with a descriptive-analytical literature review method. Data were collected through a systematic review of scholarly articles, books, and research reports from various academic databases, such as Google Scholar and ScienceDirect. Analysis was conducted using content analysis techniques to identify and categorize various forms of technology used in online learning and their impact on the learning process and outcomes. Research results show that the utilization of digital technology plays a crucial role in supporting the effectiveness of online learning. Learning Management Systems (LMS) such as Moodle and Google Classroom provide structured classroom management features. Video conferencing platforms like Zoom and Microsoft Teams enable synchronous interaction. Artificial Intelligence (AI) technology supports personalized learning and automatic feedback. Virtual Reality (VR), Augmented Reality (AR), and gamification increase student engagement through immersive and interactive learning. In addition, online collaboration and data-driven assessment can be enhanced through platforms like Google Workspace and learning analytics. Mobile learning applications such as Coursera and Khan Academy also provide flexibility in self-directed learning. These findings indicate that the appropriate integration of technology can significantly improve the quality of online learning.